2022
DOI: 10.3390/jpm12040547
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of New-Onset Atrial Fibrillation and Associated Outcomes in Patients with Sepsis: A Systematic Review and Meta-Analysis

Abstract: Background: New-onset atrial fibrillation (NOAF) is a common complication in patients with sepsis, although its prevalence and impact on outcomes are still unclear. We aim to provide a systematic review and meta-analysis on the prevalence of NOAF in patients with sepsis, and its impact on in-hospital mortality and intensive care unit (ICU) mortality. Methods: PubMed and EMBASE were systematically searched on 26 December 2021. Studies reporting on the prevalence of NOAF and/or its impact on in-hospital mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 57 publications
3
14
0
3
Order By: Relevance
“…A systematic review and meta-analysis of 31 studies showed how new-onset AF represents a common complication in COVID-19 patients, being found in up to 8% of hospitalized patients, and also showed that AF is associated with a significant increase in the risk of all-cause mortality [ 5 ]. These results are in accordance with those found in other similar scenarios, such as sepsis [ 6 , 7 , 8 ] and community-acquired pneumonia [ 9 ], and offer an interesting outlook on the relationship between infections, inflammation, and cardiovascular disease, all being connected by thrombosis [ 10 ]. On the other hand, Protasiewicz et al reported a retrospective analysis on the impact of anticoagulation before the SARS-CoV-2 infection on the clinical course and outcome of COVID-19; while being limited by low statistical power, the authors did not find any statistically significant difference according to the anticoagulation status [ 11 ].…”
supporting
confidence: 90%
“…A systematic review and meta-analysis of 31 studies showed how new-onset AF represents a common complication in COVID-19 patients, being found in up to 8% of hospitalized patients, and also showed that AF is associated with a significant increase in the risk of all-cause mortality [ 5 ]. These results are in accordance with those found in other similar scenarios, such as sepsis [ 6 , 7 , 8 ] and community-acquired pneumonia [ 9 ], and offer an interesting outlook on the relationship between infections, inflammation, and cardiovascular disease, all being connected by thrombosis [ 10 ]. On the other hand, Protasiewicz et al reported a retrospective analysis on the impact of anticoagulation before the SARS-CoV-2 infection on the clinical course and outcome of COVID-19; while being limited by low statistical power, the authors did not find any statistically significant difference according to the anticoagulation status [ 11 ].…”
supporting
confidence: 90%
“…Já em Meierhenrich et al, 9 foram selecionados apenas pacientes com choque séptico e foi encontrada uma incidência de 46% de FA nova, 10 vezes mais do que aqueles pacientes com sepse sem evolução para choque. Entretanto, mais recentemente, a metanálise conduzida por Corica et al, 18 demonstrou prevalência de FA nova em pacientes sépticos de 13,5%, semelhante à do presente estudo. Essa variabilidade pode ser explicada pelos inúmeros critérios de inclusão e diferentes populações abordadas.…”
Section: Discussionunclassified
“…Moreover, inflammation may be a key driver of the increased risk of newAF in these patients [ 7 ], as observed also in other clinical scenarios [ 31 ]. Unsurprisingly, the onset of AF has been repeatedly described during sepsis [ 6 , 32 ], a condition in which increased expression of inflammatory cytokines (including Interleukin-6 (IL-6), IL-8, and Tumor necrosis factor α) is thought to contribute to left atrial electric remodeling which in turns increases the risk of AF [ 7 , 33 , 34 ]. This pathophysiological hypothesis can be applied also to CAP and may explain the findings observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among cardiac arrhythmias, new-onset atrial fibrillation (newAF)—defined as a new or first detectable episode of a chaotic and irregular atrial rhythm, whether symptomatic or not [ 5 ], usually confirmed through 12-lead ECG—can be frequently observed during acute respiratory infection and has been repeatedly associated with increased mortality in CAP patients, especially in critically ill ones [ 6 ]. The pathophysiological link between newAF and infections could be explained by the systemic inflammatory response and the pro-inflammatory cytokines cascade causing both structural and electrical atrial remodeling which increases the risk for newAF [ 7 ].…”
Section: Introductionmentioning
confidence: 99%